2007
DOI: 10.1542/peds.2006-1995
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Placement Stability on Behavioral Well-being for Children in Foster Care

Abstract: Objective-Although prior research has demonstrated that frequent placement changes can negatively impact outcomes of children in foster care, it is equally possible that a child's baseline attributes may impact both their capacity to achieve placement stability and their subsequent wellbeing. The goal of this study was to disentangle the effect of a child's baseline problems at entry into foster care on subsequent placement stability and behavioral outcomes in order to separate out the direct impact of placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
273
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 469 publications
(289 citation statements)
references
References 21 publications
14
273
0
2
Order By: Relevance
“…Current institutional policies and practices of the child welfare system often prevent many children from experiencing continuity of care while in foster care. 89 In a US study, Rubin, et al 90 noted that 70% of multiple placements while in foster care were because of child welfare administration demands and issues related to new staff. The current study found that adults who were in foster care as children reported high rates of maltreatment during foster care.…”
Section: Discussionmentioning
confidence: 99%
“…Current institutional policies and practices of the child welfare system often prevent many children from experiencing continuity of care while in foster care. 89 In a US study, Rubin, et al 90 noted that 70% of multiple placements while in foster care were because of child welfare administration demands and issues related to new staff. The current study found that adults who were in foster care as children reported high rates of maltreatment during foster care.…”
Section: Discussionmentioning
confidence: 99%
“…Annual rates of placement change across children in foster care are estimated to be between 0.55 and 0.62, with some children changing placements multiple times per year (40,41). Placement instability has been associated with hypothalamicpituitary-adrenal axis dysregulation (42), internalizing and externalizing behavior problems (43,44), and increased emergency department use (38). Notably, these increased negative symptoms and behaviors appear to contribute to placement instability as well (43).…”
Section: Instability Nonparental Care and Healthmentioning
confidence: 99%
“…3 Research has identified several child, family, and system characteristics that predict placement instability and failure to achieve timely permanence for children in foster care: being older, being placed in care with a nonrelative (versus a relative), and having a prior history of removal, placement instability, and/or residential treatment. [4][5][6][7][8][9][10][11][12][13] One of the most robust predictors of negative placement and permanency outcomes is a child's behavioral and mental health problems. [7][8][9][10]12,13 Although it is widely believed that placement changes are harmful and that permanency is beneficial for children involved in the child welfare system, it has been difficult to establish empirically the relationship between placement characteristics and child well-being, in part because many studies have not controlled for children' s baseline functioning.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] One of the most robust predictors of negative placement and permanency outcomes is a child's behavioral and mental health problems. [7][8][9][10]12,13 Although it is widely believed that placement changes are harmful and that permanency is beneficial for children involved in the child welfare system, it has been difficult to establish empirically the relationship between placement characteristics and child well-being, in part because many studies have not controlled for children' s baseline functioning. A handful of studies that have controlled for baseline functioning have found that placement instability increases behavior problems, especially for children with high numbers of placement changes, 12,14 but that early behavior problems also predict later behavior problems, after controlling for placement changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation